Psychometric Properties and Validation of the EMOTICOM Test Battery in a Healthy Danish Population - Dam, Vibeke H.; Thystrup, Christa K.; Jensen, Peter S.; Bland, Amy R.; Mortensen, Erik L.; Elliott, Rebecca; Sahakian, Barbara J.; Knudsen, Gitte M.; Frokjaer, Vibe G.; Stenbæk, Dea S. (Frontiers in Psychology, 2019)
Disruptions in hot cognition, i.e. the processing of emotionally salient information, are prevalent in most neuropsychiatric disorders and constitute a potential treatment target. EMOTICOM is the first comprehensive neuropsychological test battery developed specifically to assess hot cognition. The aim of the study was to validate and establish a Danish language version and reference data for the EMOTICOM test battery. To evaluate the psychometric properties of 11 EMOTICOM tasks, we collected data from 100 healthy Danish participants (50 males, 50 females) including retest data from 49 participants. We assessed test-retest reliability, floor and ceiling effects, task-intercorrelations, and correlations between task performance and relevant demographic and descriptive factors. We found that test-retest reliability varied from poor to excellent while some tasks exhibited floor or ceiling effects. Intercorrelations among EMOTICOM task outcomes were low, indicating that the tasks capture different cognitive constructs. EMOTICOM task performance was largely independent of age, sex, education, and IQ as well as current mood, personality, and self-reported motivation and diligence during task completion. Overall, many of the EMOTICOM tasks were found to be useful and objective measures of hot cognition although select tasks may benefit from modifications to avoid floor and ceiling effects in healthy individuals.